EDUCATIONAL PURSUITS AND GOALS FOR ADOLESCENTS WHO ARE BLACK AND IN CARE: INSIGHTS FROM YOUTH, CAREGIVERS, AND CHILD WELFARE STAFF IN ONTARIO, CANADA - Christa Sato; Daniel Kikulwe (International Journal of Child, Youth & Family Studies)
It is well established in the literature that Black children and youth-in-care are disproportionately overrepresented in Ontario’s child welfare system. Additionally, Black youth experience structural challenges with the education system. However, there is a lack of Canadian literature that explores the educational experiences of Black children while receiving child welfare services. This study examined the reports of youth, child welfare staff, and caregivers on the educational experiences of Black youth-in-care. In-depth interviews exploring the educational needs and goals of Black youth-in-care were conducted with 13 participants (3 child welfare staff, 6 caregivers, and 4 youth). Findings highlight that Black youth-in-care experience labelling, hypervisibility and invisibility, and harassment and bullying, all of which had an impact on how they navigated the school system, and contributed to internalized stereotypes and feelings of isolation and unbelonging. The findings also identify strategies for innovation and promoting the educational success of Black youth-in-care.